Strengthening Anti-Corruption Character Based on Local Wisdom of the Malind Tribe in Elementary School Students - Hallatu, Trinovianto George Reinhard (Indonesian Values and Character Education Journal, 2023)
Corruption is a problem that is being faced by almost all countries in the world. One way to prevent corruption is to strengthen anti-corruption character education. This study aims to analyze the basic anti-corruption values ​​based on local wisdom of the Malind tribe to strengthen the anti-corruption character for elementary school students in Merauke. This type of research is descriptive qualitative, with observation and interview data collection techniques. Observations were made by observing the environment and the life of the Malind tribe. Interviews were conducted with the adat leader, the adat secretary, as well as several Malind tribal communities. The results showed that in everyday life there are several local wisdoms or attitudes of the Malind tribe which are the same as anti-corruption values. These values ​​are honest (hekaymayan), caring (anim bekatik), independent (anepkaitika), discipline (wetkatane), responsibility (weglah), hard work (payaa), simplicity (hayakla), courage (yaman), and just ( sangahawekla). These values ​​can be included in lessons at school in order to form an anti-corruption character towards students.